Horizontal and vertical axis wind turbines on existing jacket platforms: Part 2 – Retrofitting activities. (June 2022) - Mendes, Paulo; Correia, José A.F.O.; Arrojado, João; Heo, Taemin; Fantuzzi, Nicholas; Manuel, Lance
Abstract: A fast-expanding number of oil & gas companies are planning to shift investment to renewable energy projects, with offshore wind expected to spearhead this campaign. Now, with global demand for wind power growing, major oil and gas companies are diversifying their portfolios by developing offshore wind and the companies that provide services to offshore fossil fuel platforms are seeing a new market rising in their wake. Changing the future service life of oil and gas platforms by converting them into support structures for offshore wind turbines requires some retrofitting measures in order to reduce the cost of maintenance, increase reliability and improve the structural performance of the integrated turbine-platform system. Five different retrofitting solutions are presented, four of which are related to the substructure and one is related to a modified wind turbine. The retrofitting solution related to the substructure was the only solution that guaranteed safety. This study dealing with the retrofitting activities is the continuation of a previous work where the repurposing of oil and gas platforms for offshore wind energy generation was investigated.